2009
DOI: 10.1093/rheumatology/kep067
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age at disease onset in the outcome of paediatric systemic lupus erythematosus

Abstract: The risk of damage is inversely correlated with age at disease onset in pSLE. The poorer outcome observed in younger children may be explained by a more severe disease expression, may be a higher infectious susceptibility, and a more aggressive therapy, particularly within the first 6 months of disease course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
49
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 41 publications
6
49
1
3
Order By: Relevance
“…In other conditions that accompany SS, the rampant tooth decay that occurs as a consequence of the xerostomia is very difficult to manage but several recent studies have now shown that oral glandular secretions and sicca complaints can be improved with HCQ (Dawson et al 2005;Descloux et al 2009;Cankaya et al 2010).…”
Section: Sjögren's Syndromementioning
confidence: 99%
“…In other conditions that accompany SS, the rampant tooth decay that occurs as a consequence of the xerostomia is very difficult to manage but several recent studies have now shown that oral glandular secretions and sicca complaints can be improved with HCQ (Dawson et al 2005;Descloux et al 2009;Cankaya et al 2010).…”
Section: Sjögren's Syndromementioning
confidence: 99%
“…[16][17][18] Studies have reported that juvenile-onset SLE patients tend to have more aggressive presentation and course, with higher rates of organ involvement and lower life expectancy than adult-onset SLE patients. [19][20][21][22][23][24] Late-onset SLE patients tend to have more insidious onset of disease and tend to have less major organ involvement and more benign disease course. 25 However, they have a poorer prognosis than patients who developed SLE before the age of 50 years, because of the generally higher frequency of comorbid diseases and higher organ damage, due to aging and longer exposure to ''classical'' vascular risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] Although cSLE may be associated with more frequent use of corticosteroids and other immunosuppressive agents than adult-onset SLE, which may in turn relate to disease damage, 3,6,15 limited data regarding therapies in early versus later onset cSLE are available. 10 The objective of this study was to examine differences between early and later onset cSLE patients followed at one academic center. The early onset cohort consisted of pre-pubertal patients diagnosed with cSLE prior to their 12th birthday, and was compared with a race and ethnicity matched cohort of cSLE patients who were pubertal at diagnosis.…”
Section: Introductionmentioning
confidence: 99%